Dual strategy for reduced signal‐suppression effects in matrix‐assisted laser desorption/ionization mass spectrometry imaging. (28th October 2019) - Bastrup, Joakim; Birkelund, Svend; Asuni, Ayodeji A.; Volbracht, Christiane; Stensballe, Allan
Abstract : Rationale: The molecular complexity of tissue features several signal‐suppression effects which reduce the ionization of analytes significantly and thereby weakens the quality of matrix‐assisted laser desorption/ionization (MALDI) mass spectrometry (MS) imaging (MALDI imaging). We report a novel approach in MALDI imaging by reducing signal‐suppression effects for the analysis of beta‐amyloid (Aβ) plaques, one pathological hallmark of Alzheimer's disease (AD). Methods: We analyzed Aβ proteoforms from postmortem AD brains and brains from transgenic mice (APPPS1‐21) overexpressing familial AD mutations by combining two techniques: (1) laser capture microdissection (LCM) to accumulate Aβ plaques and (2) phosphoric acid (PA) as additive to the super‐2, 5‐dihydroxybenzoic acid matrix. Results: LCM and MALDI‐MS enabled tandem mass spectrometric fragmentation of stained Aβ plaques. PA improved the signal‐to‐noise (S/N) ratio, especially of the Aβ1‐42 peptide, by three‐fold compared with the standard matrix additive trifluoroacetic acid. The beneficial effect of the PA matrix additive in MALDI imaging was particularly important for AD brain tissue. We identified several significant differences in Aβ plaque composition from AD compared with APPPS1‐21, underlining the value of reducing signal‐suppressing effects in MALDI imaging. Conclusions: We present a novel strategy for overcoming signal‐suppression effects in MALDI imaging of Aβ proteoforms.